Analysis Capabilities Understanding Mathematics Students MTsN 1 Probolinggo on Algebraic Shape Calculation Operation Material - Lilik Nur Susilowati; Shofia Hidayah (Civiliza Publishing, Indonesia., 2026)
This research is motivated by the low ability of students' mathematical understanding of algebraic form calculation operations. Students tend to have difficulty understanding concepts, identifying elements of algebraic forms, and applying these concepts in problem solving. This study aims to describe the mathematical comprehension ability of grade VII MTsN 1 Probolinggo students in algebraic form calculation operation material. This study uses a qualitative approach with a descriptive type of research. The subjects of this study were 21 students in grade VII MTsN 1 Probolinggo, of which 6 students were selected as in-depth interview subjects based on the categories of cognitive ability (high, medium, and low). Data collection was carried out through a description test consisting of seven questions based on seven indicators of mathematical comprehension ability and strengthened by semi-structured interviews. The results of the study show that the mathematical comprehension ability of grade VII MTsN 1 Probolinggo students in the operation material calculating algebraic forms is quite good, but it is not evenly distributed in all indicators. High-category students were able to master almost all indicators well, although they were slightly constrained in explaining conceptual meaning in a contextual manner. Middle-category students have mastered basic concepts and identification of like-minded syllables, but encounter obstacles when constructing complex mathematical models and simplifying algebraic fractions. Meanwhile, the complex. Meanwhile, students in the lower group still experience fundamental obstacles in mastering concepts, differentiating same-sex tribes, and working on procedures.